THE ABUNDANCE OF ZOOPLANKTON AS SECONDARY PRODUCER AT AWUR BAY IN THE NORTHERN CENTRAL JAVA SEA - Hadi Endrawati; Muhammad Zainuri; Hariyadi . (JOURNAL OF COASTAL DEVELOPMENT, 2000)
The diversity of zooplankton {as Secondary Producer) were observed at seagrass, mangrove and coral reef area at Awur Bay, in Jepara Waters. The observation were made fom August, 13 to September, 10, 2000, atfour daibr intervals : at 09.00 A.M., 12.00 noon ,3.00 P.M. and 6,00 PM. The zooplankton abundance at the seagrass area are 33 73—6497 individuals/ml with an average of 5329 individuals/ml , at the mangrove area 4132»5970 individuals/mg with an average of 5177 individuals/mj , and at the coral reef area 3061-4079 with average of 3599 individuals/ml. The zooplankton di\}ersity at the seagrass area are 2,1594»2,2917, with an average of 2,2289, at the mangrove area 2, 0925»2,4962 with an average cf 2,5130 and at the coral reefarea 1,9227- 2,1181 with an average of 2,0306 On the basis of the zooplankton abundance and diversity at seagrasr, mangrove and coral reef area of the Awur Bay, the averages at the Jepara Waters can be regarded as an indicator of marine productivity. The three locations observed displays a direct interre lation as the habitat of zooplankton.